A novel multifunctional O-methyltransferase implicated in a dual methylation pathway associated with lignin biosynthesis in loblolly pine - Li, Laigeng (The National Academy of Sciences of the USA, 1997)
S-adenosyl-l-methionine (SAM)-dependent O-methyltransferases (OMTs) catalyze the methylation of hydroxycinnamic acid derivatives for the synthesis of methylated plant polyphenolics, including lignin. The distinction in the extent of methylation of lignins in angiosperms and gymnosperms, mediated by substrate-specific OMTs, represents one of the fundamental differences in lignin biosynthesis between these two classes of plants. In angiosperms, two types of structurally and functionally distinct lignin pathway OMTs, caffeic acid 3-O-methyltransferases (CAOMTs) and caffeoyl CoA 3-O-methyltransferases (CCoAOMTs), have been reported and extensively studied. However, little is known about lignin pathway OMTs in gymnosperms. We report here the first cloning of a loblolly pine (Pinus taeda) xylem cDNA encoding a multifunctional enzyme, SAM:hydroxycinnamic Acids/hydroxycinnamoyl CoA Esters OMT (AEOMT). The deduced protein sequence of AEOMT is partially similar to, but clearly distinguishable from, that of CAOMTs and does not exhibit any significant similarity with CCoAOMT protein sequences. However, functionally, yeast-expressed AEOMT enzyme catalyzed the methylation of CAOMT substrates, caffeic and 5-hydroxyferulic acids, as well as CCoAOMT substrates, caffeoyl CoA and 5-hydroxyferuloyl CoA esters, with similar specific activities and was completely inactive with substrates associated with flavonoid synthesis. The lignin-related substrates were also efficiently methylated in crude extracts of loblolly pine secondary xylem. Our results support the notion that, in the context of amino acid sequence and biochemical function, AEOMT represents a novel SAM-dependent OMT, with both CAOMT and CCoAOMT activities and thus the potential to mediate a dual methylation pathway in lignin biosynthesis in loblolly pine xylem.